Relationship of smartphone addiction with musculoskeletal system pain, depression and sleep quality in university students - Turgay, Türkan; Yılbaş, Barış (Journal of Dependence, 2025)
Objective: The aim of this study is to investigate the relationship between musculoskeletal pain, poor sleep quality, depression, and smartphone use severity in university students. Method: 121 students studying at our university were included in the study. Smartphone addiction levels were evaluated with the smartphone addiction scale-short form (SAS-SV), sleep quality and disorder Pittsburgh Sleep Quality Index (PSQI), and musculoskeletal pain prevalence using the Scandinavian Musculoskeletal Questionnaire. Beck Depression Inventory (BDI) was applied to determine the presence and severity of depressive complaints of the participants. Results: The mean age of the participants was 22.99±2.31 years, and 71 (58.7%) were female. The SAS-SV mean score of the females was higher than the males (p=0.002). 66.1% of the university students who participated in the study thought that the use of smartphones negatively affected their academic performance. The most common musculoskeletal pain in the study participants was back (64.5%), low back (63.6), neck (54.5%) and shoulder (49.6%) pain Statistically, significantly higher scores were obtained from SAS-SV in patients who had pain in the neck, shoulder, hand, upper back, low back, hip, knee, and foot in the last 1 year compared to those without pain. A statistically significantly higher mean score from SAS-SV was determined among the participants who scored 6 and above in PSQI compared to those who scored 5 and below. Those who scored 16 and below in BDI had a significantly lower score in SAS-SV than those who scored 17 and above. Conclusion: Smartphone use may be a potential risk factor for musculoskeletal symptoms, poor sleep quality, and depression. In our study, it was found that the effect of smartphone addiction on the musculoskeletal system was independent of depression and poor sleep quality. Our study reveals the importance of raising awareness about smartphone addiction and its consequences among university students.